Weapons, funds, and international recognition in the War of the Pacific. The role of the legation of Peru in France and England after the fall of Lima (1881-1884) - Abanto Chani, Julio César (2023)
This research focuses on knowing the actions deployed by the Peruvian legation in France and England after the fall of Lima in the hands of the Chilean army and in the midst of a deep political anarchy that influenced the setting of the objectives of the foreign policy of the parallel governments that Peru had between 1881 and 1883, specifically in obtaining funds and weapons for the regimes of the presidents Francisco García Calderón, Nicolás de Piérola, Lizardo Montero and Miguel Iglesias. Despite the deep political division, the Peruvian legation continued with the execution of the orders of Lima and Arequipa as part of foreign policy, although with increasing autonomy towards the end of the war. In this sense, unpublished information from various historical sources will be analyzed, including the archives of the Ministry of Foreign Affairs of Peru, the National Library of Peru, and the Riva Agüero Institute.